Introducing the Non-Religious in Alcoholics Anonymous - Munro, Zachary A. (Implicit religion, 2019)
The religious dimensions of Alcoholics Anonymous (AA) have long caused tensions for the non-religious involved in the fellowship. In response to these challenges, an increasing number of secular meeting groups have begun emerging, offering non-religious approaches to AA's Twelve Step model of recovery. Drawing on qualitative interview and observational data with members of secular groups located in Toronto, Canada, this article explores how non-religion manifests as meaningful difference in the lives of the non-religious navigating AA. As religion is encountered, participants describe how their non-religious identities became problematized, characterized as active impediments to recovery, and how non-religion is often experienced as a source of struggle and conflict. Despite such challenges, as the non-religious persist in active engagement with AA they participate in new labours of nonreligion, producing new agential spaces and new interpretations and expressions of AA's Twelve Step model of recovery. In recognizing non-religion as meaningful difference and attending to the ways it manifests and operates within AA, this article argues that attention to non-religion in AA provides new opportunities for both research into the substantial features of non-religion and integrative paths for the non-religious in AA and Twelve Step fellowships more broadly.